2017
DOI: 10.1038/ncomms14571
|View full text |Cite
|
Sign up to set email alerts
|

Disorder-induced single-mode transmission

Abstract: Localized states trap waves propagating in a disordered potential and play a crucial role in Anderson localization, which is the absence of diffusion due to disorder. Some localized states are barely coupled with neighbours because of differences in wavelength or small spatial overlap, thus preventing energy leakage to the surroundings. This is the same degree of isolation found in the homogeneous core of a single-mode optical fibre. Here we show that localized states of a disordered optical fibre are single m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…For a disordered optical fiber, the scaling characteristics of the MA-PDF with respect to the transverse dimensions of the fiber are completely different from the periodic case. Disorder-induced TAL localizes most of the guided modes across the transverse structure of the disordered fiber and each mode provides a narrow guiding channel [34]. Figure 3 shows the MA-PDF for a TALOF where all parameters involved in the disordered structure are exactly the same as Fig.…”
mentioning
confidence: 99%
“…For a disordered optical fiber, the scaling characteristics of the MA-PDF with respect to the transverse dimensions of the fiber are completely different from the periodic case. Disorder-induced TAL localizes most of the guided modes across the transverse structure of the disordered fiber and each mode provides a narrow guiding channel [34]. Figure 3 shows the MA-PDF for a TALOF where all parameters involved in the disordered structure are exactly the same as Fig.…”
mentioning
confidence: 99%
“…In particular, Refs. [80], [81] recently pointed out that the presence of a strong disorder in TAL fibers can be exploited to obtain high-quality wavefronts. Abaie et al [81] showed, in agreement with the theoretical analysis of Ref.…”
Section: B Spatial Coherence and Illuminationmentioning
confidence: 99%
“…Disorder [1] is generally considered detrimental for imaging or optical information transport, nevertheless, complex systems can disclose extraordinary physical properties, allowing the confinement of light [2], and enabling high resolution imaging techniques [3]. The task of driving light at the nanoscale is usually fulfilled by homogeneous waveguides or photonic crystals supporting a band gap [4]: completely ordered structures which allow to tailor the light flow.…”
Section: Introductionmentioning
confidence: 99%